Persepsi Periset Pusat Riset Teknologi dan Proses Pangan BRIN terhadap Pengelolaan Arsip Hasil Penelitian - Indrawardani, Ken Fitria; Kamajati, Dhatu; Aulianto, Dwi Ridho (Perpustakaan dan Arsip Universitas Gadjah Mada, 2024)
Documents from research activities (substantive archives) at Research Center for Food Technology and Processing (PRTPP)-National Research and Inovation Agency (BRIN) contain essential information regarding research progress in Food Technology and Processes. Referring to this, researchers need to submit hardcopy archives of research results to archive managers so that archival principles can manage the information. However, only a few researchers have proposed these archives to archive managers. This research aims to discover why researchers at PRTPP do not submit hardcopy archives of research results to archive managers at PRTPP.The research method used is descriptive qualitative, with primary data and information obtained through questionnaires supported by interviews with PRTPP researchers. The research results concluded that the most significant causes were guaranteeing the confidentiality of data and information, the availability of archive storage space, and the security of archive access. It is necessary to make handing over hardcopies of research results archives a priority within the scope of work of the Regional Archives Services team, and it is hoped that they can synergize with PRTPP policymakers. To achieve this target, providing permanent archive storage facilities and conducting outreach to researchers is necessary. In addition, it is necessary to prepare SOPs to make it easier for researchers to collect hard copies of research results archives and a joint commitment between researchers and records managers in improving the management of research results archives in the future